How Socioeconomic, Health Seeking Behaviours, and Educational Factors Are Affecting the Knowledge and Use of Antibiotics in Four Different Cities in Asia - Susan Ka Yee Chow; Xingjuan Tao; Xuejiao Zhu; Atsadaporn Niyomyart; Edward Choi (MDPI AG, 2021)
Antibiotic resistance is occurring widely throughout the world and is affecting people of all ages. Socioeconomic factors, education, use of antibiotics, knowledge of antibiotics, and antibiotic resistance were assessed in four cities in Asia, namely Hong Kong, Shanghai, Hangzhou, and Bangkok. A survey using cluster sampling was used in 2021 to collect data on 642 subjects. Hongkongers used less antibiotics and were knowledgeable about using antibiotics to treat diseases, while Shanghainese were knowledgeable about antibiotic resistance. The multi-linear regression model reported that respondents who lived in Hong Kong (β = 0.744 (95% CI: 0.36-1.128), Shanghai (β = 1.65 (95% CI: 1.267-2.032), and Hangzhou (β = 1.393 (95% CI: 0.011-1.775) (reference group: Bangkok), who had higher scores on antibiotics knowledge (β = 0.161 (95% CI: 0.112-0.21)), higher educational attainment (β = 0.46 (95% CI: 0.296-0.625)), and who were more likely to consult a doctor on using antibiotics (β = 1.102 (95% CI: 0.606-1.598)), were more likely to give correct answers about antibiotic resistance, p < 0.001. Older respondents were less likely to answer the items correctly (β = −0.194 (95% CI: −0.333-−0.055), p < 0.01. When educating the public on the proper use of antibiotics and antibiotic resistance, multiple strategies could be considered for people from all walks of life, as well as target different age groups.